Analisis Hasil Belajar Efektif Dari Penerapan Smart Learning - Rafi Hidayat (Jurnal Sistem Cerdas, 2018)
A smart city is an urban place where information technology and digital communication are used to increase knowledge and utilize technology, intellectual resources and real to improve the quality of life. One of the main areas of smart cities is intelligent learning and education, which is a new concept of technology-enhanced learning. Measuring the effectiveness of smart education depends on measuring the desired learning outcomes. This paper suggests the main key features that must be considered when developing learning analysis tools to measure and assess each subject's learning outcomes. And it shows the relationship between an intelligent learning environment, learning outcomes and learning analysis.